(untitled) (Jurnal Bahasa, 2020)
Act The Sexual Offences Against Children Act (Act 792) was passed in April 2017 and gazetted on 10 July, 2017. Act 792 was drafted to deal with technological advancements, and new terms for sexual offences relating to child grooming and masochistic abuse were introduced. Some of these terms are new to Malaysians and the meaning of those terms may not be fully understood by legal practitioners. Hence, the purpose of this study is to analyse these new terms from the perspective of semantics. A descriptive method employing the content analysis approach was applied to examine and discuss the meanings of the new terms used in Act 792. The new terms are elaborated on from a legal perspective with reference to several Acts, including the Penal Code 1976, and the Pedoman Umum Pembentukan Istilah Bahasa Melayu (2004) is used as the main reference for elaboration from a language point of view. This study concludes that there are five new terms which require elaboration from a linguistic and legal angle in order to protect children in sexual and pedophilic crimes. These are: kebinatangan (bestiality); sadis and masokis (sadistic or masochistic abuse); pengantunan (child grooming); and amang (assault). Keywords: Act 792, terminology, language aspect, legal language, sexual offences against children